2021
DOI: 10.1108/jfm-11-2020-0088
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of public hospital buildings in Nigeria – an assessment of current practices and policy options

Abstract: Purpose The recent COVID-19 pandemic has exposed the declining conditions of many of the hospital buildings, especially in developing countries. Past studies have shown inadequate maintenance practices but how far regarding Nigerian public hospital buildings is yet to receive empirical research. This paper aims to investigate the underlying issues leading to inadequate maintenance practices and proffers policy options to improve Nigerian public hospital buildings via an unexplored dimension. Design/methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Findings from this paper were compared with the existing literature for robust discussion. Regarding the inadequate water pressure or poor maintenance of “active” fire prevention mechanisms, findings agree with Ong and Suleiman (2015b), Ebekozien et al (2020a, 2020b, 2021) and Kuriakose et al (2020). Ong and Suleiman (2015b) found that the health-care houses faced challenges in fire safety management such as blockage of fire safety systems, inadequate installation of fire measures or outdated fire safety technology and documentation problems.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Findings from this paper were compared with the existing literature for robust discussion. Regarding the inadequate water pressure or poor maintenance of “active” fire prevention mechanisms, findings agree with Ong and Suleiman (2015b), Ebekozien et al (2020a, 2020b, 2021) and Kuriakose et al (2020). Ong and Suleiman (2015b) found that the health-care houses faced challenges in fire safety management such as blockage of fire safety systems, inadequate installation of fire measures or outdated fire safety technology and documentation problems.…”
Section: Discussionsupporting
confidence: 86%
“…Ong and Suleiman (2015b) found that the health-care houses faced challenges in fire safety management such as blockage of fire safety systems, inadequate installation of fire measures or outdated fire safety technology and documentation problems. Ebekozien et al (2020a, 2020b, 2021) found inadequate maintenance and absence of maintenance plans for public hospital buildings in Developing countries setting. This challenge is further compounded with the lax implementation and enforcement of training and re-training of basic fire safety precautionary measures and recovery in some of the health-care facilities (Ebekozien et al , 2020a, 2020b).…”
Section: Discussionmentioning
confidence: 99%
“…One of the key deficiencies has been a lack of cooperation between life cycle phases, where information transfer has been insufficient and, in particular, has been incomplete in the later phases (Harkonen et al , 2019; Halttula et al , 2020). Several studies report information- and quality-related maintenance problems arising in the design and construction phases (Waziri, 2016; Hassanain, et al , 2019; Ebekozien et al , 2022; Hauashdh et al , 2022), and life cycle costs and maintenance have been studied extensively (Ebekozien, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Future studies should consider adopting a sequential exploratory mixed method. It allows generalisability (Creswell et al, 2018;Ebekozien et al, 2021b). The authors recognised that this type of research design enhances scholars to authenticate the results from the oral data.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%